mir-124-5p Regulates Phagocytosis of Human Macrophages by Targeting the Actin Cytoskeleton via the ARP2/3 Complex - Herdoiza Padilla, Estefania; Crauwels, Peter; Bergner, Tim; Wiederspohn, Nicole; Förstner, Sabrina; Rinas, Rebecca; Ruf, Anna; Kleemann, Michael; Handrick, René; Tuckermann, Jan; Otte, Kerstin; Walther, Paul; et al. (Frontiers in Immunology, 2019)
Phagocytosis is a cellular process crucial for recognition and removal of apoptotic cells and foreign particles, subsequent initiating an appropriate immune responses. The process of phagocytosis is highly complex and involves major rearrangements of the cytoskeleton. Due to its complexity and importance for tissue homoeostasis and immune responses it is tightly regulated. Over the last decade microRNAs (miRNAs) have emerged as important regulators of biological pathways including immune response by fine tuning expression of gene regulatory networks. In order to identify miRNAs implicated in the regulation of phagocytosis, a systematic screening of all currently known, human miRNAs was performed using THP-1 macrophage-like cells and serum-opsonized latex beads. Of the total of 2566 miRNAs analyzed, several led to significant changes in phagocytosis. Among these, we validated miR-124-5p as novel regulator of phagocytosis. Transfection with miR-124-5p mimics reduced the number of phagocytic cells as well as the phagocytic activity of phorbol-12-myristate-13-acetate (PMA)-activated THP-1 cells and ex vivo differentiated primary human macrophages. In silico analysis suggested miR-124-5p targets genes involved in regulation of the actin cytoskeleton. Transcriptional analyses revealed that expression of genes encoding for several subunits of the ARP2/3 complex, a crucial regulator of actin polymerization, is reduced upon transfection of cells with miR-124-5p. Further in silico analyses identified potential binding motifs for miR-124-5p in the mRNAs of these genes. Luciferase reporter assays using these binding motifs indicate that at least two of the genes (ARPC3 and ARPC4) are direct targets of miR-124-5p. Moreover, ARPC3 and ARPC4 protein levels were significantly reduced following miR-124-5p transfection. Collectively, the presented results suggest that miR-124-5p regulates phagocytosis in human macrophages by directly targeting expression of components of the ARP2/3 complex.